VD_FINDINFO Décision / 2019 / 692 vom 13. August 2019 - VD Tribunal cantonal (2019)
DROIT D'ÊTRE ENTENDU, INDEMNITÉ ÉQUITABLE, TORT MORAL, DOMMAGE PUREMENT ÉCONOMIQUE | 29 al. 2 Cst., 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH)